(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
This article examines the theoretical and practical aspects of developing innovative competence among future teachers within the modern educational system. It explores the integration of the cluster approach into the educational process, the pedagogical effectiveness of innovative technologies, and the importance of creative and critical thinking in teacher training. The study also highlights the role of teachers’ speech culture, personal development clusters, and creative activities in shaping innovative competence.